Effectiveness of Young Coconut Water And carrots Juice Against the Scale of Dysmenorrhea on The Teenage Princess - Candra Wahyuni (Universitas STRADA Indonesia, 2023)
Dysmenorrhea is a pain in the abdomen that originates from cramps in the uterus and occurs during menstruation. Dysmenorrhea is divided into two, called primary dysmenorrhea if the underlying cause is not found, and called secondary dysmenorrhea if the cause is an abnormality. The aim of this study was to find out the difference in the effectiveness of giving young coconut water and carrot juice against the scale of dysmenorrhea in teenage princesses. Pre-experimental research design with research approach two group comparison pre-test and post-test design. The research population was the entire teenage princess of class XI in SMAN 3 City of Kediri with a sample of 32 respondents using purposive sampling techniques. The instruments used are the observation sheet and the FRS pain scale. The data were analyzed using the Wilcoxon and Mann-Whitney tests. The results of the study showed that there was a difference in the effectiveness of the administration of young coconut water and carrot juice against the dysmenorrhea scale with a p-value of 0.047 < α. (0,05). The findings of this study showed that giving young coconut water (p-value 0,000) was more effective in decreasing dysmenorrhea in teenage girls compared to giving carrot juice. (p-value 0,008).